PENATALAKSANAAN DAN FOLLOW UP BERKALA PADA AMETROPIA AMBLIOPIA - Rares, Laya M. (Jurnal Biomedik : JBM, 2013)
Abstract: Amblyopia is a decline of visual acuity, unilateral or bilateral, even after a maximal correction and is not directly related to any structural disorders of the eye or posterior visual pathway. We reported the case of an 8-year-old boy with bilateral amblyopia treated with a full correction eye glass therapy. The patient underwent a general eye examination, a set of tests related to the causes of amblyopia, and an eye glass correction to obtain BCVA in both eyes. The results showed VOD 5/60 S-2.50 = C-2.50 x 180o 6/18, VOS 4/60 S-2.00 = C-2.75 X 180o 6/15, and normal intraoccular pressures of both eyes by palpation. Light reflex of ODS was normal with no RAPD. The eyeball positions were normal without any anomaly. The eyeball movements were good in all directions, while the Ishihara color blindness test showed a normal result. The spacious view was normal, and the visible image of funduscopy had no anomaly. The patient was treated wih a correction of anomaly refraction by using eyeglasses as the initial treatment. In the case that there is no significant improvement in the initial therapy, a patching therapy and a periodical follow-up in the process of the eyesight rehabilitation is suggested. Conclusion: Based on all the tests performed, the diagnosis of this patient was bilateral amblyopia. It was expected that by the resumption of wearing eyeglasses for the anomaly refraction correction and eyesight rehabilitation, and with periodical follow-ups the patient’s condition would improve. Keywords: bilateral amblyopia, anomaly refraction, full correction therapy.   Abstrak: Ambliopia adalah penurunan ketajaman penglihatan unilateral atau bilateral walaupun telah diberikan  koreksi terbaik, yang tidak berhubungan langsung dengan kelainan struktural mata ataupun jaras penglihatan posterior. Kami melaporkan kasus seorang anak laki-laki berusia 8 tahun dengan ambliopia bilateral yang telah diberikan terapi kacamata full correction. Pada kasus ini telah dilakukan pemeriksaan mata menyeluruh, serangkaian tes yang berkaitan dengan penyebab ambliopia, dan koreksi kaca mata untuk mencapai BCVA (Best Corection Visual Aquity) pada kedua mata. Hasil pemeriksaan memperihatkan VOD 5/60 S-2.50 C-2.50 x180 6/12, VOS 4/60 S-2.00 C -2.75x180 6/15, tekanan intraokuler (dengan palpasi) mata kanan dan kiri normal, RAPD (-), ortoforia, tes warna normal, serta lapang pandang normal dan segmen posterior dalam batas normal. Koreksi kelainan refraksi dengan kacamata sebagai penanganan awal dan direncanakan untuk terapi patching bila tidak terdapat kemajuan yang bermakna dari terapi awal, serta follow up berkala dalam proses rehabilitasi penglihatan. Simpulan: Berdasarkan hasil pemeriksaan yang telah dilakukan, diagnosis pada kasus ini ambliopia bilateral. Setelah terapi koreksi kelainan refraksi menggunakan kaca mata dan rehabilitasi penglihatan dengan follow up berkala diharapkan visus optimal dapat tercapai. Kata kunci: ambliopia bilateral, refraksi anomali, terapi full correction.